The Impact of Trade Policy on Uganda's Coffee Export Growth Rate - Belind Lucy Aketit (Uganda Christian University, 2023)
International trade has been considered as an important tool to boost the economic growth of Uganda and achieve its aspirations (A Transformed Ugandan Society from a Peasant to a Modern and Prosperous Country by 2040). This research was intended to investigate the effect of trade policy on Uganda's coffee export growth rate and the ultimate impact on economic growth (1995 - 2015). Several scientific research, and some economic theories, advocate a positive relationship between trade and economic growth. This study aimed to examine the impact of Tariff barriers, Non-Tariff Barriers, and Free Trade Policy on Uganda’s coffee export growth rate and the ultimate impact on the economic growth of Uganda. In order to analyze a 20-year time series of data on coffee export growth and economic growth expressed as Gross Domestic Product (GDP), from 1995 to 2015 that was collected from the World Bank databases, the quantitative research approach was applied. The impact of tariff Barriers, Non-Tariff Barriers, and Free Trade Policy on Uganda’s Coffee Exports wasexamined using econometric analysis and Ordinary Least Square linear regression. The study's conclusions showed a significant and positive relationship between Uganda's coffee export growth rate (GDP), Tariff Barriers by Uganda, and Free Trade Policy. However, they also showed a negative relationship between coffee export growth rate (GDP) and Non-Tariff Barriers imposed by other countries in the East African Community. The study recommends continuing to execute export- or import-led policies while promoting the BUBU in Uganda initiative, the National export strategy, and technology to add value to coffee exports and as well as diversify Ugandan exports in general.
This is a dissertation.